2012
DOI: 10.3168/jds.2011-4468
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the metabolic profiles of noncoagulating and coagulating bovine milk

Abstract: We hypothesize that, through milk composition and different milk metabolites, it is possible to characterize the technological properties (e.g., coagulation) of milk. In this research, liquid chromatography mass spectrometry was used to obtain profiles of low molecular weight organic compounds in 143 milk samples. The metabolic profiles of milk from cows were correlated with their coagulation properties. Using multivariate data analysis methods, we demonstrated that the metabolic profiles of the milk were corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…unit = arbitrary unit. (Harzia et al, 2012). The role directly played by carnitine in the rennet-induced coagulation process thus remains unclear.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…unit = arbitrary unit. (Harzia et al, 2012). The role directly played by carnitine in the rennet-induced coagulation process thus remains unclear.…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, SCC, acidity (Ikonen et al, 2004), and variability in minor milk compounds, such as minerals and citrate (Udabage et al, 2001;Tsioulpas et al, 2007), have also been associated with differential milk coagulation properties. Additionally, oligosaccharides have been correlated with rennet-induced coagulation properties (Harzia et al, 2012). It has been shown previously that variations exist in coagulation properties in milk from different cows, where some cows produce well-coagulating (WC) milk and some produce poorly coagulating or NC milk (Ikonen et al, 1999;Glantz et al, 2010;.…”
Section: Introductionmentioning
confidence: 98%
“…Milk acidity, and in particular titratable acidity (TA), affects the aggregation rate of paracasein micelles, the reactivity of rennet, and the rate of syneresis (De Marchi et al, 2009a); as reported by Formaggioni, Malacarne, Summer, Fossa, and Mariani (2001), milk with low acidity is generally considered unsuitable for cheese-making, because of negative effects on the rheology of the rennet curd and on the textural properties of the cheese paste. Moreover, several studies have investigated the favourable relationships between TA and milk coagulation properties (MCP; Cassandro et al, 2008;De Marchi, Dal Zotto, Cassandro, & Bittante, 2007;De Marchi et al, 2009a;Harzia et al, 2012;Penasa et al, 2010;Toffanin, De Marchi, Penasa, Pretto, & Cassandro, 2012) and cheese yield (De Marchi, Bittante, Dal Zotto, Dalvit, & Cassandro, 2008;Pretto, De Marchi, Penasa, & Cassandro, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The milk samples for mass spectrometry analyses were prepared and analysed as previously described by Harzia et al (2012). The milk samples for mass spectrometry analyses were prepared and analysed as previously described by Harzia et al (2012).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the amount and composition of milk produced, milk coagulation ability, the basis of cheese making, is also an important trait. Different laboratories have studied the effect of diet on milk coagulation properties (Malossini et al 1996; Guinee et al 2001), and differences in metabolic profiles of raw milk with different coagulation ability have also been noted (Sundekilde et al 2011; Harzia et al 2012). But still, to date, there is a lack of studies describing the effects of changing the glycogenic precursors on milk coagulation properties and metabolic profile.…”
Section: Introductionmentioning
confidence: 99%